Transforming service learning through critical consciousness: From charitable assistance toward empowerment praxis - Tangel, Karen Imelda Goretti (DRPM UNY, 2025)
Service Learning (SL) has long been utilized in educational settings to foster social responsibility and community engagement among students. However, without a critical framework, SL often remains a charitable activity that perpetuates unequal power dynamics between students and the communities they serve. This study examines how the concept of critical consciousness, or conscientization, can transform SL from a charitable model to one focused on empowerment and social change. Through a theoretical analysis of Paulo Freire’s critical pedagogy, the study argues that SL must move beyond providing services to addressing the root causes of societal issues. The study proposes a three-stage SL framework: deconstructing assumptions, engaging in authentic dialogue, and implementing praxis through problem-posing methodology. The findings emphasize that by integrating critical consciousness, SL can shift from merely addressing symptoms to challenging underlying social injustices. This transformation not only empowers both students and communities but also creates sustainable change through collaborative problem-solving. The study concludes that critical consciousness is essential for reshaping SL into a tool for social justice, where the relationship between students and communities is built on mutual respect, shared learning, and long-term engagement.